2017
DOI: 10.22550/rep75-1-2017-14
|View full text |Cite
|
Sign up to set email alerts
|

MOOCs for in-service teachers: The case of Uganda and lessons for Africa

Abstract: This report discusses steps for the integration and adoption of information and communication technologies (ICT) in Uganda schools. Barriers of ICT adoption for teachers were determined through surveys at three schools in Eastern Uganda. Teachers identified lack of familiarity of ICT resources and lack of ICT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…furthermore, Boga & McGreal [21] reported their experience with how Cousera platform was used to provide opportunity for the enhancement and development of ICT skills in Sub-Saharan Africa to prepare them for the evolving knowledge economy. MOOCs as capacity building vehicles include the Teachers E-learning Portal (TEP) for enhancing the teacher's digital literacy and life-long learning capabilities in Uganda [17], The Teacher Education for Sub-Saharan Africa (TESSA), also known as TESSA MOOCs [40] which focused on Kenyan Teachers and Teacher Educators. The predominant themes for the narrative analyses also include opportunity for innovative credentialing [47]; MOOCs revolution implications for African Higher Education (Carvalho & Woldegiyorgis [49]; MOOCs for addressing African evaluation capacity [42]; Boosting African Higher Education through shared MOOCs [57] and the advocacy for a wholly African MOOCs (MOOCs for Africa by Africa [45]).…”
Section: Disparate Forms Of Moocs Implementation Models In Ssamentioning
confidence: 99%
See 1 more Smart Citation
“…furthermore, Boga & McGreal [21] reported their experience with how Cousera platform was used to provide opportunity for the enhancement and development of ICT skills in Sub-Saharan Africa to prepare them for the evolving knowledge economy. MOOCs as capacity building vehicles include the Teachers E-learning Portal (TEP) for enhancing the teacher's digital literacy and life-long learning capabilities in Uganda [17], The Teacher Education for Sub-Saharan Africa (TESSA), also known as TESSA MOOCs [40] which focused on Kenyan Teachers and Teacher Educators. The predominant themes for the narrative analyses also include opportunity for innovative credentialing [47]; MOOCs revolution implications for African Higher Education (Carvalho & Woldegiyorgis [49]; MOOCs for addressing African evaluation capacity [42]; Boosting African Higher Education through shared MOOCs [57] and the advocacy for a wholly African MOOCs (MOOCs for Africa by Africa [45]).…”
Section: Disparate Forms Of Moocs Implementation Models In Ssamentioning
confidence: 99%
“…Given that, there are conflicting positions regarding the low patronage of MOOCs in SSA. Some authors argued that "MOOCs offered on Cousera platforms were more successful among the young, male, well-educated and employed students in developed contexts [17,18].Whereas, Ngimwa and Wilson, [11] reported that low technological level in Africa do not impede the adoption of educational technology, contrary to previous research studies [19][20][21]. Therefore, it is important to dig further to shed more light on the evolution of a disruptive technology such as MOOCs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that teachers are motivated by being provided inservice training, and such training improves their teaching practices. Oyo et al (2017) have investigated the outcome after implementing the massive computer literacy open online courses (MOOC) through 'the teachers' e-learning portal. The authors found that Ugandan teachers get interested and improve their performance.…”
Section: The Motivation For the Studymentioning
confidence: 99%
“…De igual manera, se evaluó la actitud en el 27.58% de los artículos (2,4,9,14,19,22,25,26), puesto que la mayoría de los docentes no tienen la suficiente confianza para utilizar las TIC por temor a ser "burlados" por sus alumnos (Colás et al, 2016); si bien, algunos estudios reportan que los docentes tienen una actitud favorable hacia las TIC vinculado con la disposición de recibir capacitación, lo cual influye en el nivel de sus competencias digitales (Linne, 2020;Palacios-Rodríguez y Martín-Párraga, 2021). La actitud y motivación son dos elementos que se deben mantener de manera constante en las instituciones, otorgando facilidades a los docentes a través de cursos con el fin emplear las TIC en su quehacer educativo (Oyo et al, 2017).…”
Section: Tabla 3 Factores Que Influyen En El Nivel De Las Competencia...unclassified